1980
DOI: 10.1002/zaac.19804670107
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen an Nickeloxid‐Mischkatalysatoren. II Katalytische Eigenschaften von NiO/SiO2‐Katalysatoren

Abstract: Die katalytischen Eigenschaften von NiO/SiO2‐Katalysatoren unterschiedlicher Zusammensetzung, deren Herstellung durch Tränken und Fällen erfolgte, wurden bei der Dimerisierung von Ethen und der Isomerisierung von 1‐Buten untersucht. Während bei der Dimerisierung von Ethen an den Fällungskatalysatoren in Abhängigkeit von der Zusammensetzung ein Maximum der katalytischen Aktivität bei 60 Mol‐% NiO festgestellt wurde, sind die durch Tränken hergestellten Katalysatoren nahezu unwirksam. Im Unterschied dazu erhöht … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…A considerable number of papers have dealt with the problem of nickel-containing catalysts for ethylene dimerization. [1][2][3][4][5][6][7][8][9][10][11] One of the remarkable features of this catalyst system is its activity in relation to a series of n-olefins. In contrast to usual acid-type catalysts, nickel oxide on silica or silica-alumina shows a higher activity for a lower olefin dimerization, particularly for ethylene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of papers have dealt with the problem of nickel-containing catalysts for ethylene dimerization. [1][2][3][4][5][6][7][8][9][10][11] One of the remarkable features of this catalyst system is its activity in relation to a series of n-olefins. In contrast to usual acid-type catalysts, nickel oxide on silica or silica-alumina shows a higher activity for a lower olefin dimerization, particularly for ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to usual acid-type catalysts, nickel oxide on silica or silica-alumina shows a higher activity for a lower olefin dimerization, particularly for ethylene. [1][2][3][4][5][6]12 It has been suggested that the active site for dimerization is formed by an interaction of a low-valent nickel ion with an acid site. 9,13 It has been reported that the dimerization activities of such catalysts are related to the acidic properties of surface and low valent nickel ions.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of papers have dealt with the problem of nickel-containing catalysts for ethylene dimerization. [1][2][3][4][5][6][7][8][9][10][11] One of the remarkable features of this catalyst system is its activity in relation to a series of n-olefins. In contrast to usual acid-type catalysts, nickel oxide on silica or silicaalumina shows a higher activity for a lower olefin dimerization, particularly for ethylene.…”
Section: Introcuctionmentioning
confidence: 99%
“…In contrast to usual acid-type catalysts, nickel oxide on silica or silicaalumina shows a higher activity for a lower olefin dimerization, particularly for ethylene. [1][2][3][4][5][6]12 It has been suggested that the active site for dimerization is formed by an interaction of a low-valent nickel ion with an acid site. 9,13 In fact, nickel oxide, which is active for C 2 H 4 -C 2 D 4 equilibration, acquires an activity for ethylene dimerization upon addition of nickel sulfate, which is known to be an acid.…”
Section: Introcuctionmentioning
confidence: 99%
“…A considerable number of papers have dealt with the nickel-containing catalysts for ethylene dimerization. 17,[20][21][22][23][24][25][26][27][28] One of the remarkable features of this catalyst system is its activity in relation to a series of n-olefins. In contrast to usual acid-type catalysts, nickel oxide on silica or silica-alumina shows a higher activity for a lower olefin dimerization, particularly for ethylene.…”
Section: Introductionmentioning
confidence: 99%